Attempting inclusive practice: perspectives of physical educators and adapted physical educators. Issue 3 (1st September 2020) - Wilson, Wesley J.; Theriot, Elizabeth A.; Haegele, Justin A.
ABSTRACT: Inclusive education has become a global area of study, yet research has highlighted challenges with inclusive practices among teachers in integrated physical education contexts. The purpose of this study was to examine physical education and adapted physical education teachers' perspectives on how they attempt inclusive practice in integrated physical education. Using a qualitative description design, 78 teachers (30 physical education, 48 adapted physical education) responded to an open-ended survey item related to their inclusive practice. While the teachers believed that they did the best they could with their inclusive practices, which often relied on collaborative efforts to meet students' needs, they highlighted challenges of inadequate support, unqualified staff, and integrating students with severe disabilities. To mitigate these challenges, teacher education can better prepare preservice PE and APE teachers to navigate the sociopolitics of working in public schools and to collaborate effectively with other personnel to meet the needs of students.